Organizational climate, social support predictors of work life balance in employees - Hidayat, Novi; Rismawati, Rismawati; Ikromi, Ziyadi Ali (Privietlab, 2025)
Work-life balance is a critical concern in contemporary workplaces, as it affects both individual well-being and the overall efficiency of the organization. A good organizational climate can foster a supportive work environment, while support from supervisors, colleagues, and family is expected to help employees manage the demands of their professional and personal lives. This study seeks to assess the impact of organizational climate and social support on employees’ work-life balance. Using quantitative methodology, this study utilized a survey administered to employees selected through a simple random sampling technique, resulting in a sample size of 100 respondents. The questionnaires in this study were adapted and modified by the Work-Life Balance Scale (WLBS), Questionnaire of Frequency and Satisfaction with Social Support (QFSSS), and Organizational Climate Measure (OCM), with Cronbach’s alpha coefficients of 0.770, 0.731, and 0.836, respectively. Data were analyzed using multiple regression analysis at a significance level of 0.05. The results of this study indicate that organizational climate and social support act as significant predictors of work-life balance among employees. This study highlights the important role of a supportive work environment and social networks in facilitating the achievement of a healthy work-life balance among employees. The practical implications of these findings can inform organizational management in developing policies and cultures that encourage employee work-life balance.